Texas charter school legislation and the evolution of open-enrollment charter schools. - Ausbrooks, Carrie Y. Barron; Barrett, Edith J.; Daniel, Theresa (Education Policy Analysis Archives, 2005)
This article chronicles the evolution of legislation for Texas open-enrollment charter schools to their implementation by demonstrating how these schools have (or have not) used their freedom from state-mandated requirements to develop innovative learning environments as well as to bring innovative curricula into the classroom. The investigative focus was on an analysis of Texas open-enrollment charter school legislation, from 1995 (74th legislative session) to the 77th legislative session in 2001, and the characteristics of the state's 159 open-enrollment charter schools that were in operation during the 2001-2002 academic year. The authors found that charter school legislation has changed in response to concerns of all involved, and focuses on the need for balance between choice, innovation, and public accountability. Although charter schools are free from most state regulations, legislators were clearly interested in ensuring that this freedom does not impede charter schools' ability to provide a quality education to all students who attend them. The currently operating open-enrollment charter schools in Texas are more racially and economically segregated than other public schools in the state, and charter schools that targeted students most at risk for dropping out of school (and returning students who had previously dropped out) differ from other schools in their stated teaching methods. Teacher turnover remains significantly greater than that for other public schools in the state. However, it does not appear to be specifically associated with schools that target disadvantaged students or minority students. The schools' mission statements suggest that innovative school environments are a factor in school design. Texas is poised to continue along the public education choice model. Charter school legislation provides a framework upon which charter schools may build to meet the educational needs of the students who choose to attend them, including the freedom to be creative in meeting students' unique needs. Questions remain about how and why charter schools exist and the contributions they make to the overall public school system, including whether charters are making a difference in what and how much children are learning.